Pelatihan Perencanaan, Penganggaran, Penatausahaan dan Pelaporan Keuangan Nagari - Fitra, Halkadri; Sebrina, Nurzi; Khatimah, Husnil; Syofyan, Efrizal; Helmy, Herlina (Manaruko: Jurnal Pengabdian Masyarakat, 2024)
The training on Planning, Budgeting, Administration, and Financial Reporting of Nagari in Nagari Kamang Hilia, Agam Regency was attended by 25 participants and aimed to enhance the capacity of Nagari officials in managing village finances efficiently and accountably. This program included an in-depth understanding of the Village Financial System (Siskeudes), which consists of modules for planning, budgeting, implementation, administration, and reporting. Additionally, the training emphasized the principles of transparent, accountable, participatory, orderly, and disciplined financial management. With this training, it is expected that Nagari officials will be able to manage village funds more effectively, in line with applicable regulations, and increase transparency of information to the public. This activity also aims to ensure that all Nagari officials have a uniform understanding in carrying out their duties, ultimately improving the quality of village financial management in Nagari Kamang Hilia.